Economics for today - Tucker, Irvin B. (Thomson Learrning, 2005)
Straightforward and student-friendly, Tucker, ECONOMICS FOR TODAY, The most pedagogically-rich and engaging principles text on the market. Ideal for students of varying levels of skills and preparation, ECONOMICS FOR TODAY presents learners with the basics of economic principles and the context to apply them to their everyday lives. The 4th edition continues Tucker's tradition of using a unique textual and visual learning system to concisely present and reinforce core concepts, then assess student comprehension.